Arabic corpus linguistics - McEnery, Tony 1964-; Hardie, Andrew ca. 20./21. Jh; Younis, Nagwa ca. 20./21. Jh (Edinburgh University Press, 2019)
This book demonstrates the advantage of a corpus based approach to Arabic, and presents an overview of current research on the Arabic language within corpus linguistics. Dealing not only with modern standard Arabic, the book also considers classical and colloquial forms
Keywords: Arabisch; Korpus -- Linguistik; Arabic language / Grammar, Comparative; Corpora (Linguistics); Aufsatzsammlung